Modul Pendampingan IbuHamil sebagai Inovasi Peningkatan Pengetahuan Pencegahan Anemia - Fidyah Aminin Aminin; Utami Dewi; Nurniati T. R.; Vina Jayanti (Politeknik Kesehatan Kementerian Kesehatan Semarang, 2019)
Maternity deaths in pregnant women are associated with anemia. Efforts to overcome anemia in pregnant women have not achieved the optimum results. One of them is caused by the low level of pregnant women knowledge and adherence in consuming iron supplements and in this case family support is needed. The government has distributed iron suplementation but the knowledge of pregnant women and husbands regarding prevention of anemia is still lacking. To increase knowledge, it is necessary to have a accompaniment module for prevention of anemia. The aim of the study was to determine the differences in knowledge of pregnant women’s husband about prevention of anemia in pregnant women before and after the module was given.It used Quasi experiment research method pre-posttest with control group design. The treatment groupgiven health education using the module while the control group only provided health education without the module. The sample in this research were the husband of pregnant women in Independent Midwifery Practice, 47 respondents in treatment group and 47 respondents in control group . Data analysis used Wilcoxon. There was difference knowledge of pregnant women’s husband before and after the given module with p value 0.000.Giving module increase knowledge of pregnant women’s husband in anemia prevention.It was expected that health workers use module to increase pregnant women’s husband knowledge about anemia prevention.